Pindar's poetic “I” and the muses: metaphorical role characterization in different genres - Kuhn-Treichel, Thomas (The classical journal, 2020)
This paper offers a fresh perspective on the representation of the Muse(s) in Pindar. Two recent studies addressing this issue have argued for a clear distinction between the epinikia and the cult songs. This paper aims to reassess this approach and to offer a different perspective on the problem, focusing on the metaphors applied to the relationship with the Muse(s). While the image as drawn by Kantzios and Maslov emerges as simplistic, some of the metaphors can be linked to the given genre because they are based on analogies to the context of performance, which also enhance the cognitive effect of the poems.
Gesehen am 02.06.2021